Punishment in paradise : race, slavery, human rights, and a nineteenth-century Brazilian penal colony - Beattie, Peter M., 1963- (Duke University Press, 2015)
Peter M. Beattie provides a detailed examination of the nineteenth-century Brazilian island penal colony Fernando de Noronha, in which he shows how it serves as a metaphor for Brazilian society and was key to Brazil's abolishment of slavery.